Book Review: Rebuilding Leviathan: Party Competition and State Exploitation in Post-Communist Democracies by Anna Grzymala Busse, 2007, Cambridge: Cambridge University Press - Vukovic, Ivan (Studies of Transition States and Societies, 2010)
Rebuilding Leviathan: Party Competition and State Exploitation in Post-Communist Democracies by Anna Grzymala Busse, 2007, Cambridge: Cambridge University Press